2014
DOI: 10.4236/oje.2014.43016
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Changes in the Lesser Flamingos Population (<i>Phoenicopterus minor</i>) in Relation to Phytoplankton Abundance in Lake Manyara, Tanzania

Abstract: A study on seasonal variations in the abundance of Lesser Flamingo (Phoenicopterus minor) in relation to phytoplankton abundance in lake Manyara was conducted for a period of fourteen consecutive months (July 2007 to August 2008). The aim was to relate the temporal variability in the phytoplankton species abundance and diversity of the lake to the population size of the Lesser Flamingo. Lesser Flamingo population numbers were obtained from monthly ground surveys whereby the lake was subdivided into defined cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 25 publications
(28 reference statements)
3
23
1
Order By: Relevance
“…As noted earlier, available literature asserts the occurrence of toxic strains of cyanobacteria and their impacts in some parts of the United Republic of Tanzania. To date, the only documented reports/incidences in Tanzania is the mass fatality of Lesser Flamingos in saline lakes in Arusha and Manyara Region (Fyumagwa et al., 2013; Kihwele et al., 2014; Kotut et al., 2006; Lugomela et al., 2006; Nonga et al., 2011).…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…As noted earlier, available literature asserts the occurrence of toxic strains of cyanobacteria and their impacts in some parts of the United Republic of Tanzania. To date, the only documented reports/incidences in Tanzania is the mass fatality of Lesser Flamingos in saline lakes in Arusha and Manyara Region (Fyumagwa et al., 2013; Kihwele et al., 2014; Kotut et al., 2006; Lugomela et al., 2006; Nonga et al., 2011).…”
Section: Main Textmentioning
confidence: 99%
“…Studies (e.g. Lugomela et al., 2006; Nonga et al., 2011; Mdegela et al., 2011; Fyumagwa et al., 2013; and Kihwele et al., 2014) in the United Republic of Tanzania have demonstrated the occurrence of toxin producing-cyanobacteria in specific regions. However, these studies are not sufficient to conclusively judge CyanoHABs dynamics and their link with climatic and hydrological variation, because most of them are event-driven, for example, post-mortem of Flamingo mortality in Lake Manyara.…”
Section: Introductionmentioning
confidence: 99%
“…Phytoplankton levels lessened from 606 Units/mL in 2010 to 187 Units/mL in 2012. However, there was an increment in the phytoplankton levels to 321 Units/mL in 2013 which could have been caused by alterations in phytoplankton species composition and diversity that in turn affected their abundance due to alterations in the chemical and physical properties of the water (Kihwele et al 2014).…”
Section: Phytoplankton Levelsmentioning
confidence: 99%
“…The in situ preferred food organisms consist of filamentous cyanobacteria, mainly Spirulina platensis , as well as benthic diatoms [ 1 , 2 ]. Many studies showed that temporal fluctuations in lesser flamingo populations are related to the changes in the abundance and diversity of phytoplankton species [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ]. The occurrence of Spirulina spp.…”
Section: Introductionmentioning
confidence: 99%
“…was associated with the increase in the abundance of lesser flamingos. It was observed that changes in the lesser flamingo numbers were influenced by the changes in the abundance and availability of their preferred food [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ]. All flamingo species (Phoenicopteridae) feed their nestlings using crop secretions, called crop milk, originating from esophageal glands, for up to six months [ 12 , 13 , 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%